Modified Alliance-Focused Training with Doubling as an integrative approach to improve therapists’ competencies in dealing with alliance ruptures and prevent negative outcomes in psychotherapy for depression: study protocol of a randomised controlled multicentre trial - Anne Daubmann; Antonia Zapf; Antje Gumz; Frank Jacobi; Denise Kästner; Laurence Reuter; Carmen Martinez Moura; Klarissa Ehlers; Catherine F Eubanks; John Christopher Muran; Timothy Anderson; Ramona Stöckl; et al. (BMJ Open, 2025)
Introduction Alliance ruptures constitute a high risk of premature treatment termination and poor psychotherapy outcome. The Alliance-Focused Training (AFT) is a promising transtheoretical approach to enhance therapists’ skills in dealing with alliance ruptures.Methods and analysis To evaluate the effectiveness of Modified AFT with doubling (MAFT-D), a randomised, patient and evaluator-blinded, multicentre trial was designed comparing MAFT-D (delivered to trainee therapists and supervisors) and psychotherapy training/treatment as usual (TAU) for therapists (n=120) and their patients with depressive disorders (n=240). A total of 17 cooperating centres, each offering either cognitive-behavioural or psychodynamic psychotherapy training, will contribute to recruitment. Stratification by centre (both for therapists and patients) and hence therapeutic approach (cognitive-behavioural vs psychodynamic psychotherapies), and by comorbid personality disorder (yes vs no, for patients) will be carried out. The two hierarchically ordered primary hypotheses are: In MAFT-D compared with TAU, a stronger reduction of depressive symptoms and a lower rate of patient dropout is expected from baseline to 20 weeks after baseline. Follow-up assessments are planned at 35 weeks, 20 months and 36 months postbaseline to evaluate the persistence of effects. Secondary patient-related and therapist-related outcomes as well as predictors, moderators and mediators of change will be investigated. Mixed models with repeated measures will be used for the primary analyses.Ethics and dissemination Ethical approvals were obtained by the institutional ethics review board of the main study centre as well as by review boards in each federal state where one or more cooperating centres are located (secondary votes). Following the Consolidated Standards of Reporting Trials statement for non-pharmacological trials, results will be reported in peer-reviewed scientific journals and disseminated to patient organisations and media.Trial registration number DRKS00014842; https://drks.de/search/de/trial/DRKS00014842.